Crustal structure across the eastern North American margin from ambient noise tomography. Issue 13 (3rd July 2017) - Lynner, Colton; Porritt, Robert W.
Abstract: Passive tectonic margins, like the eastern North American margin (ENAM), represent the meeting of oceanic and continental material where no active deformation is occurring. The recent ENAM Community Seismic Experiment provides an opportunity to examine the crustal structure across the ENAM owing to the simultaneous deployment of offshore and onshore seismic instrumentation. Using Rayleigh wave phase and group velocities derived from ambient noise data, we invert for shear velocity across the ENAM. We observe a region of transitional crustal thicknesses that connects the oceanic and continental crusts. Associated with the transitional crust is a localized positive gravitational anomaly. Farther east, the East Coast magnetic anomaly (ECMA) is located at the intersection of the transitional and oceanic crusts. We propose that underplating of dense magmatic material along the bottom of the transitional crust is responsible for the gravitational anomaly and that the ECMA demarks the location of initial oceanic crustal formation. Key Points: We use ambient noise tomography at both onland and offshore stations to examine crustal structure across the eastern North American margin We observe three structural portions of the passive ENAM: continental crust, transitional crust, and oceanic crust The East Coast magnetic anomaly demarks the boundary between continental and oceanic crustal material